Módulo didáctico para prácticas de electrónica industrial bajo plataforma Arduino (2020)
The objective of this degree project is the construction of a didactic module for industrial automation practices of the Electromechanical Engineering program attached to Mechanical Engineering of the University Antonio Nariño campus Neiva, taking into account that the development of the classes is incompletely presented that the practical component cannot be adequately performed since the equipment is not suitable for the employees by the students.